2022
DOI: 10.3389/fphar.2022.913408
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Sodium Alginate/Velvet Antler Blood Peptides Hydrogel Promoted Wound Healing by Regulating PI3K/AKT/mTOR and SIRT1/NF-κB Pathways

Abstract: Skin wound healing is a principal clinical challenge, and it is necessary to develop effective alternative treatments. Excessive inflammatory response is linked to delayed healing. This study was the first to report a multi-functional chitosan/sodium alginate/velvet antler blood peptides (VBPs) hydrogel (CAVBPH) and explore its potential mechanism to promote wound healing. The results showed that CAVBPH possessed desirable characteristics including thermo-sensitivity, antioxidation, antibacterial activity, bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…46 CS-based wound dressings have been shown to exert therapeutic effects by activating the PI3K/AKT pathway. 25,47 Interestingly, this work confirmed that CAVBPH more prominently exerted a pro-angiogenic effect than CAH via activating the PI3K/AKT/mTOR/HIF-1α/VEGFA pathway (Figure 7).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…46 CS-based wound dressings have been shown to exert therapeutic effects by activating the PI3K/AKT pathway. 25,47 Interestingly, this work confirmed that CAVBPH more prominently exerted a pro-angiogenic effect than CAH via activating the PI3K/AKT/mTOR/HIF-1α/VEGFA pathway (Figure 7).…”
Section: Discussionsupporting
confidence: 62%
“…Previously, CS/SA polymer was shown to be more efficient in promoting wound repair than either CS or SA alone, and CS/SA composite hydrogel possessed excellent physicochemical properties to support it as a promising wound dressing scaffold. 25,42 The results of in vitro evaluation showed that CAVBPH possessed good porous breathability, swelling, biodegradability, antioxidant property, biocompatibility, biosafety, and release behavior of VBPs (Figures 1 and 2). Subsequently, we topically applied CAVBPH to the wound surface, on the one hand, to avoid direct contact of the wound with the outside, and on the other hand to continuously provide VBPs for wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the suppression of the NF-κB pathway is considered a promising therapeutic approach for regenerative medicine. In these senses, numerous systems based on hydrogels have been successfully developed for targeting mtROS and inhibiting of NF-κB activity for regenerative medicine [ 29 , 30 , 31 ]. In addition, the abovementioned drugs (antibiotics, NSADs, growth factors, and morphogens) can be included directly in the hydrogel.…”
Section: Introductionmentioning
confidence: 99%